Development of poly(2-ethyl-2-oxaline) based water-soluble binder for injection molding of stainless steel powder - (:unkn) unknown (ELSEVIER SCI LTD, 2007)
The successful use of new binder system for the injection molding of stainless steel powder as a test material is described. The binder system comprises a major fraction of poly(2-ethyl-2-oxaline) of various molecular weights and a minor fraction of polypropylene (PP). The weight fraction of poly(2-ethyl-2-oxaline) in the binder was maintained to be 77 wt%. The rheological properties of feedstock were investigated systematically. The binder system used provides satisfactory mixture stability, excellent moldability and reasonably fast water leaching and thermal debinding rates. Poly(2-ethyl-2-oxaline) was removed by leaching in water at 65 degrees C for 6.5 h. The remaining binders were bourn out by thermally at 600 degrees C for an hour. Brown parts were sintered at 1350 degrees C for an hour in pure H-2. Debinded and sintered samples were examined by SEM and optical microscopy. (c) 2006 Elsevier Ltd. All rights reserved.